Questions Used By The Characters In Frozen Movie Manuscript - Indah Purwaningsih, Novita; , Agus Wijayanto, Ph.D (2017)
This research focus on the types of questions and its illocutionary meanings used by the characters in Frozen movie manuscript. The data of this research are the writing form of questions found in Frozen movie manuscript. The data source is the manuscript of Frozen movie. The researcher collects the data by documentation. Documentation is a method that is used to categories, investigate, interpret, and identify most of written documents in both private and public domain. To analyze the types of questions, the writer uses the theory of Frank (1972), while to analyze the illocutionary meanings of questions, the writer uses the theory of Searle (1969). The result shows that (1) there are three types of questions used by the characters in Frozen movie manuscript. The types of questions are yes-no question, tag question, and wh-question. The types of questions that are often used by the characters in Frozen movie manuscript with the highest percentage is Yes-No question with 60%. The second position is WH question with 36%, consisting the words what, who, why and how. The third position is tag question with 4% percentage. Those types of questions above have different illocutionary meanings. (2) There are seventeen illocutionary meanings of questions that used by the characters in Frozen movie manuscript. The illocutionary meanings of questions that are often used in the Frozen movie manuscript with the highest percentage is surprised with 26%. The second is doubt with 22%. The third is teasing with 12%. The fourth is request with 8%. The fifth are offering, interest, and anger with the same percentage which is 4%. The seventh position are invitation, protest, imagination, marriage proposal, acceptance of marriage proposal, checking, amazed, care, denying, and wedding vow with equal percentage which is 2%. Keywords: questions, the illocutionary meanings of questions